Twitter (X) and Journalistic Practices: A Case Study of Pakistani Journalists - Bhadur, Ali; Prof. Dr. Saqib Riaz (Journal of Peace, Development and Communication, 2024)
The adoption of social media platforms by journalists, particularly Twitter (X) has undergone a significant transformation with profound implications for the profession of journalism. Twitter (X), currently known as X has emerged as a vital tool in the field of journalism due to its ability to provide immediate and real-time information to a large audience. This study focuses on journalistic practices in Pakistan and aims to explore the association between the use of Twitter (X) and journalism. By surveying 300 journalists from electronic, print, and digital media in Pakistan, the study evaluates how Pakistani journalists rely on Twitter (X) for their work-related activities. The study found a strong positive relationship between Twitter (X) usage by journalists and their practices in news sourcing and dissemination. The results highlight the progressive role of Twitter (X) in shaping journalistic practices in Pakistan’s rapidly evolving digital landscape. Overall, this study draws attention to the significant link between Twitter (X) usage and journalistic practices. The study provides valuable insights into how social media platforms like Twitter (X) have transformed the journalism profession in Pakistan.